2008
DOI: 10.1128/jb.01726-07
|View full text |Cite
|
Sign up to set email alerts
|

A Set of Activators and Repressors Control Peripheral Glucose Pathways in Pseudomonas putida To Yield a Common Central Intermediate

Abstract: Pseudomonas putida KT2440 channels glucose to the central Entner-Doudoroff intermediate 6-phosphogluconate through three convergent pathways. The genes for these convergent pathways are clustered in three independent regions on the host chromosome. A number of monocistronic units and operons coexist within each of these clusters, favoring coexpression of catabolic enzymes and transport systems. Expression of the three pathways is mediated by three transcriptional repressors, HexR, GnuR, and PtxS, and by a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…First, both synonymous mutations occur in a gene predicted to encode a permease subunit of an ABC transporter, and homologues of this transport system in P. aeruginosa and P. putida are glucose inducible and responsible for glucose uptake ( Fig. 2) [21][22][23][24] . Second, the benefits conferred are specific to glucose: neither mutation significantly affected fitness on alternate sugars (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, both synonymous mutations occur in a gene predicted to encode a permease subunit of an ABC transporter, and homologues of this transport system in P. aeruginosa and P. putida are glucose inducible and responsible for glucose uptake ( Fig. 2) [21][22][23][24] . Second, the benefits conferred are specific to glucose: neither mutation significantly affected fitness on alternate sugars (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Pseudomonas, the inner membrane glucose transport component has not yet been identified; however, a specific transport component has been studied in detail for maltose uptake in E. coli (Chen et al, 2001). The downregulation of genes involved in the glucose uptake during growth on glucose and toluene was observed in P. putida KT2440 which can allow the uptake of glucose via the oxidative and phosphorylative pathway (del Castillo & Ramos, 2007;del Castillo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…del Castillo et al (11,13) showed that all sequenced Pseudomonas sp. genomes exhibit the same physical organization of the zwf/edd/pgl and eda/glk operons, with the hexR gene being transcribed divergently with respect to the edd promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose catabolic pathways in P. putida. The figure is modified from that in del Castillo et al (11,13) and del Castillo and Ramos (12) Glk, glucokinase; Zwf, glucose 6-P dehydrogenase; Pgl, 6-phosphogluconolactonase; Edd, 6-phosphogluconate dehydratase; Gcd, glucose dehydrogenase; Gad, gluconate oxidase; KguK, 2-ketogluconate kinase; KguD, 2-ketogluconate-6-phosphate dehydrogenase; G3P, glyceraldehyde 3-phosphate; Pyr, pyruvate; GnuK, gluconate kinase. FIGURE 2.…”
Section: Bacterial Strains and Plasmids Used In This Study-mentioning
confidence: 99%
See 1 more Smart Citation